Prevalence, Patterns and Implications of Gender-Based Violence against Women: Challenges and the Way Forward - Sigamani Panneer; Saranya Sundarraju; F.X. Lovelina Little Flower; Hilaria Soundari Manuel; R. Revanth (Social Work and Society)
The alarming incidence of Gender-Based Violence (GBV) highlights a critical humanitarian crisis that necessitates urgent consideration and collaborative endeavours to alleviate human suffering and advance principles of equity and security for every person. Women and teen girls are primarily affected by GBV. Patterns of GBV against women and teens are sexual, emotional, and physical. Nearly one in three women, or 736 million women and teen girls, have experienced intimate partner abuse, non-partner sexual violence, or both. A systematic review was conducted to understand the forms of GBV, and Women's knowledge of protective legislation. Studies were selected in a systematic manner to understand the interrelated forms of violence (such as physical, sexual, economic, and psychological abuse) that women and teen girls experience. The review prioritizes the best practices by highlighting the feasible approaches and priorities for addressing GBV effectively.